Managing Modularity of Service Processes Architecture - Thomas Frandsen (Copenhagen Business School (CBS), 2012)
The world is increasingly turbulent with shorter and shorter technological life cycles and more and more frequent changes in customer demand. This situation implies that flexibility and agility are crucial for producers of products and services. Much effort has been directed toward understanding innovation and the ways in which management can increase the value of innovation efforts. As a consequence, suggestions emphasizing different aspects of innovation and creativity have been put forward. However, the value of architectural knowledge for innovation is increasingly recognized as crucial with modular architectures proposed as one way of increasing the rate of innovation by introducing flexibility and agility without sacrificing efficiency. Modularity is a way to design a system with the intent of reducing its complexity by decomposing the system and reducing interdependencies between the subsystems of the system through standardized interfaces. Systems designed in this way allow for greater flexibility through recombination; however, they retain efficiency by means of standardization and scale economies from the reuse of components. For this reason modular architectures present an interesting solution to the dilemma of whether to invest in innovation or in efficiency. The topic has received much attention in the face of demands from customers for increasingly heterogeneous products and services. However, an important aspect to keep in mind is that, while decomposition is a powerful way of reducing complexity, most real systems remain only nearly decomposable (Simon, 1962) or loosely coupled rather than uncoupled (Orton & Weick, 1990)....
hdl:10398/8420
Keywords: 650